Sewage sludge composting simulation as carbon/nitrogen concentration change - Kabbashi, Nassereldeen Ahmed (Elsevier BV, 2011)
Available composting models do not describe accurately the dynamics of composting processes. Difficulty in modeling composting processes is attributed mainly to the unpredicted change in process rate caused by change in activation energy value (E). This article presented the results of an attempt made to utilize patterns of change in carbon, nitrogen and temperature profiles to model sewage sludge composting process as a multi-stage process. Results of controlled sewage sludge composting experiments were used in the study. All the experiments were carried out as batch experiments in a 300-liter Horizontal Drum Bioreactor (HDB). Analysis of the profiles of carbon, nitrogen and temperature has indicated that there were clear patterns that could be used to develop simple models of the process, the initial C/N ratio was between 7–8 and the final C/N ratio of the compost in most experiments were found to be around 15.0, indicating the compost was fully matured and could be used safely for agricultural purpose. Electrical conductivity of composting material decreased from 1.83 to 1.67 dS/m, after a period, it increased gradually from 2.01 to 2.23 dS/m and remained at around 2.33 dS/m till the end of composting. It is found that change in the concentration of total carbon can reasonably be described by three constant process rate coefficients (k1, k2, k3). It is found that the process starts with a certain process rate coefficient (k1) and continues until peak temperature is reached, then it reaches lower process (k2) in the declining phase of the thermophilic stage, and finally it proceeds with a faster process rate (k3) when maturation is reached. Change in the concentration of total nitrogen has shown to have the same patterns of change as carbon.